2017
DOI: 10.1111/ahg.12189
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of OPG/RANK/RANKL Genes as a Genetic Marker for Cardiac abnormalities in Thalassemia Major Patients

Abstract: OPG rs2073618, RANK rs75404003, and RANKL rs9594782 SNPs may predispose LVH in thalassemia patients. Patients with diastolic dysfunction showed increased levels of serum OPG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Following our findings, many studies demonstrated the relation of different polymorphisms of this axis with cardiac diseases ; Singh et al study determined that thalassemia patients having RANK rs75404003 (C > DEL), OPG rs2073618 (G > C), and minor C allele of OPG rs2073618, were at high risk for developing left ventricular hypertrophy 25 . A meta-analysis done by Song et al in 2016 showed that the OPG rs2073618 genotype is related to cardiovascular disorders such as left ventricle hypertrophy, carotid plaques, and increased risk of stroke 26 .…”
Section: Discussionsupporting
confidence: 77%
“…Following our findings, many studies demonstrated the relation of different polymorphisms of this axis with cardiac diseases ; Singh et al study determined that thalassemia patients having RANK rs75404003 (C > DEL), OPG rs2073618 (G > C), and minor C allele of OPG rs2073618, were at high risk for developing left ventricular hypertrophy 25 . A meta-analysis done by Song et al in 2016 showed that the OPG rs2073618 genotype is related to cardiovascular disorders such as left ventricle hypertrophy, carotid plaques, and increased risk of stroke 26 .…”
Section: Discussionsupporting
confidence: 77%
“…The study also found a statistically significant negative correlation between osteoprotgrin and hemoglobin and vitamin D-3 [23].…”
Section: Discussionmentioning
confidence: 54%
“…The TNFSF11 gene structure is highly conserved among mammals, consisting of five exons that span 33.9 kb in humans (10). SNPs located near TNFSF11, TNFRSF11A, and TNFRSF11B have been reported to be closely associated with Paget's disease (20), osteoporotic fractures (21), cardiovascular diseases (22), ankylosing spondylitis (11), and breast (23), and esophageal cancers (24). In this study, we showed that subjects who carried the rs9525641-C allele were more likely to develop HCV chronicity than those with the rs9525641-T allele.…”
Section: Discussionmentioning
confidence: 99%